DEVELOPMENT OF TEACHER PROFESSIONAL COMPETENCIES: TRAINING AND ASSISTANCE IN SCIENTIFIC WORK WRITING FOR JUNIOR HIGH SCHOOL TEACHERS IN MUARA ENIM DISTRICT - Purnomo, Mulyadi Eko; Sholikhah, Hani Atus; Nurhayati, Nurhayati; Suhendi, Didi; Supriyadi, Supriyadi; Saripudin, A.; Heryana, N. (LPPM Univ. Ibn Khaldun Bogor, 2024)
TEACHER PROFESSIONAL COMPETENCE DEVELOPMENT: SCIENTIFIC WORK WRITING TRAINING AND ASSISTANCE FOR SMP TEACHERS IN MUARA ENIM DISTRICT This service activity aims to make junior high school teachers in Muaraenim Regency have the ability to write scientific papers. In addition, this activity is also part of their professional development activities. The methods used are presentations, discussions, demonstrations, and recitations, and joint corrections, and revisions. Presentations, discussions, and demonstrations are intended to provide knowledge and insight along with concrete examples of the provisions of writing scientific papers in detail, section by section; also given an example of how to turn a research report into a paper or article that is ready to be published in a scientific journal. Recitation or assignment is a practice activity to make or change the form of research reports into scientific papers and scientific journal articles. This exercise is done individually and the results are discussed online via zoom or google meeting. Each participant was asked to present their work and then corrected it together by colleagues and instructors. Based on these corrections, the participants then revise their work so that they become scientific papers and/or articles that are ready to be sent/printed. The results of the service showed that there was an increase in learning outcomes from training and mentoring in writing scientific papers for 19 participants. At the beginning and end of the activity, a test was conducted in the form of self-reflection on aspects of scientific writing. The result is that there is an increase in the participant's ability to write rich scientifically before and after the activity with an N-gain of 0.58 which means moderate.